The Orphan Drug Act and the Myth of the Exclusivity Incentive - Rogyoski, Robert (Science and Technology Law Review, 2006)
For more than 20 years, the marketing exclusivity provision of the Orphan Drug Act has been hailed as a key component of the incentive for the United States’ pharmaceutical industry to develop drugs for rare disorders; this is the Official Story of the ODA. In this paper, I argue that the Official Story is a myth. Rather, the real engine for the development of drugs to treat rare disorders is the patent system.